(untitled) (Research, Society and Development, 2021)
Smoking is a pandemic in addition that beyond nicotine involves other substances, resulting in morbidity and mortality. This way, the objective of this study was to evaluate the physiological parameters of smokers undergoing treatment in Paraíba. This is a descriptive study with 100 smokers, of both sexes and over the age of 18, volunteers for treatment in the Multidisciplinary Program for the Treatment of Smokers at the Federal University of Campina Grande, Paraíba, from April to September 2018. In the first stage, smokers attended lectures about the role of all teams in the treatment (Medicine, Pharmacy, Psychology, Nutrition, Physical Education, and Dentistry). Subsequently, the pharmacy team conducted the Pharmaceutical Consultation (socioeconomic profile and physiological parameters). Of those assisted, 65 and 35% were female and male, respectively. The prevalent age group was between 46-60 years old (54%). As for physiological parameters: 47% were pre-hypertensive; casual plasma glucose of 87% was less than 200 mg/dL; 9% of the public had a circumference-hip ratio greater than 0.90 cm and 20% of the female public above 0.85 cm; the level of visceral fat in 59% of those assisted was normal. The results of the smokers’ physiological parameters showed serious risks, especially in relation to blood vessels, understanding that the practice of smoking leads to alterations and stiffening of the structures in the arteries, which can make it difficult to pump blood, with a great risk of heart disease and development of diabetes and cancer. In addition, this study contributed to the promotion of smoker’s health by minimizing the risks of problems related to tobacco using physiological parameters such as the north of pharmaceutical care.